If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2)+4x-5=7-(x+1)-6
We move all terms to the left:
3(x+2)+4x-5-(7-(x+1)-6)=0
We add all the numbers together, and all the variables
4x+3(x+2)-(7-(x+1)-6)-5=0
We multiply parentheses
4x+3x-(7-(x+1)-6)+6-5=0
We calculate terms in parentheses: -(7-(x+1)-6), so:We add all the numbers together, and all the variables
7-(x+1)-6
determiningTheFunctionDomain -(x+1)+7-6
We add all the numbers together, and all the variables
-(x+1)+1
We get rid of parentheses
-x-1+1
We add all the numbers together, and all the variables
-x
Back to the equation:
-(-x)
4x+3x-(-1x)+6-5=0
We add all the numbers together, and all the variables
7x-(-1x)+1=0
We get rid of parentheses
7x+1x+1=0
We add all the numbers together, and all the variables
8x+1=0
We move all terms containing x to the left, all other terms to the right
8x=-1
x=-1/8
x=-1/8
| -3+5q=12 | | 25=u/5-5 | | 5.27-1.34x=4x-0.871 | | 2(w-5)^2+5=23 | | 8=2y-16 | | 4/7x-1/4=8 | | 2,5x+x=70 | | 5.18x+3.56=3.4x | | 3w-11=16 | | 4x+3.6+x=1.12 | | 42=u/4+14 | | 2.5x+x=70 | | (t^2+1)/(t+2)=(t/3)+(5/t+2) | | 3x2-48=0 | | (x+1)(3-2x)=4x2-9 | | 0=16k^2+4 | | 9-7(y+6)=-3(y+5) | | (x+2)(x+5)=3x+7 | | 100p=1100-(p+) | | 3×n/20=48/80 | | 1/4X^2-4x+7=0 | | 61-4x=3x+12 | | 7x-2=10x-47 | | 2/7x+3/7=5 | | 6(1)-4x=3x+12 | | X2+4x+3=0 | | (x-5)^2-(2x-7)=8(8-x) | | -105=-7(1+2n | | -3x+3=-2x-1 | | X2-4x+3=0 | | d-4/2=3 | | N^2+20n+99=0 |